Nelson Essentials of Pediatrics - Marcdante, Karen J.; Kliegman, Robert; Schuh, Abigail M. (Philadelphia : Elsevier, 2023)
Concise, readable, and up to date, Nelson Essentials of Pediatrics, 9th Edition, provides the must-know information you need in pediatrics from the name you trust. A readable, full-color format; high-yield, targeted chapters; and thorough content updates ensure strong coverage of core knowledge as well as recent advances in the field. This focused resource is ideal for medical students, pediatric residents, PAs, and nurse practitioners in various educational and practice settings, including pediatric residencies, clerkships, and exams. Covers normal childhood growth and development, as well as the diagnosis, management, and prevention of common pediatric diseases and disorders. Contains new coverage of COVID-19, Multisystem Inflammatory Syndrome in Children (MIS-C), and Vaping-Induced Lung Injury. Includes Pearls for Practitioners at the end of each section, as well as updated immunization schedules and an expanded discussion of trauma-informed care. Features well written, high-yield coverage throughout, following COMSEP curriculum guidelines relevant to your pediatric clerkship or rotation. Uses a full-color format with images and numerous new tables throughout, so you can easily visualize complex information. Provides real-world insights from chapter authors who are also Clerkship Directors, helping you gain the knowledge and skills necessary to succeed both in caring for patients and in preparing for clerkship or in-service examinations. --
The profession of pediatrics -- Growth and development -- Behavioral disorders -- Psychiatric disorders -- Psychosocial issues -- Pediatric nutrition and nutritional disorders -- Fluids and electrolytes -- The acutely ill or injured child -- Human genetics and dysmorphology -- Metabolic disorders -- Fetal and neonatal medicine -- Adolescent medicine -- Immunology -- Allergy -- Rheumatic diseases of childhood -- Infectious diseases -- The digestive system -- The respiratory system -- The cardiovascular system -- Hematology -- Oncology -- Nephrology and urology -- Endocrinology -- Neurology -- Dermatology -- Orthopedics
Includes bibliographical references and index
Keywords: Pediatrics; Pediatrics